Consumer Participation in Co-creation: An Enlightening Model of Causes and Effects Based on Ethical Values and Transcendent Motives - Martínez-Cañas, Ricardo; Ruiz-Palomino, Pablo; Linuesa-Langreo, Jorge; Blázquez-Resino, Juan J. (Frontiers in Psychology, 2016)
In the current highly interconnected modern world, the role of consumers has changed substantially due to their active collaboration with companies in product and process innovation. Specifically, consumer participation has become key to the development of successful products and services, as companies have come to rely more and more on consumers' opinion as a source of innovative ideas and brand value. However, whereas existing research has focused on identifying the different elements involved in consumers' co-creation, there is still the need to comprehend better this complex mechanism by integrating distinct dimensional insights. With an integrative review of research into three important perspectives, one nurturing from the Service-Dominant logic, another one based on the information and communication technologies (ICTs) platforms, and (the ethical values-driven) Marketing 3.0 paradigm, this article proposes a conceptual framework in which consumers' ethical values and transcendent motivations play an important role in encouraging their engagement in co-creation activities. In this connection, and with consumers increasingly embracing the need to fulfill a social and ethical function in society, the co-creation process is here comprehended as a means to emphasize the social and moral aspects of co-creation. This article also identifies the important, supportive role of the Marketing 3.0 paradigm and Web 3.0 tools to initiate the co-creation process, as well as the important valuable benefits attained by both companies and consumers after consumers engage in this process. Importantly, these benefits are highlighted to increase when ethical products are the object of these co-creation activities. All these insights have notable implications for both research and managerial practice.